A Comprehensive Study and Development of Unified Mobile-Based Admission System for GCC Universities - Ehab Juma Adwan; Yunes Al-Aradi; Muneera Essa; Hadeel Malabari (Journal of Computing Theories and Applications, 2023)
The Gulf Cooperation Council (GCC) region has experienced tremendous growth in the higher education sector with many public but internationally recognized universities, colleges, and programs. Annually, within and outside of the GCC zone, high school students and guardians undergo repeatable and time-consuming experiences for inhomogeneous university, college, and program admission and tracking processes. This research project aims to provide a unified management tool to manage the admission and tracking process to multiple accredited GCC universities, colleges, and programs through one unified central mobile-based application. The research project aimed to achieve two objectives: exploring the GCC university admission process phenomena and developing and evaluating a unified mobile-based university admission application (denoted by HEIM) for higher education institutes' mobile applications. An Agile-SDLC methodology was employed, entailing two phases; the Exploratory phase to the phenomena of the university admission process and the development and evaluation phase of the potential mobile application. The 1st phase was based on an interview with the Ministry of Education (MOE), employing SLR and CA techniques for articles and mobile applications collection and analysis, and 1st questionnaire to collect user requirements. The 2nd phase employed several design techniques, including DFD, ERD, etc., a 2nd questionnaire to collect system requirements and coding by .NET MAUI, C#, and XAML, and a 3rd questionnaire to evaluate the usability of HEIM based on Nielsen heuristics at which the empirical findings revealed 97.7% of usability.